An Ephemeral Experience: Enrique de Benito and the Institute of Criminal Studies at the University of Valencia (1928-1930) - Hernando Serra, María Pilar (CIAN-Revista de Historia de las Universidades, 2020)
The rise of Criminology in the second half of the 19th century and in the first thirty years of the 20th century gave rise to a small but important school of Spanish criminologists. The success of correctionalism, together with the extension of the theories of the Italian Positive School, gave rise to experiences such as the Criminology Laboratory in Madrid, and the Criminology School for civil servants or complementary teachings to Criminal Law. In Valencia, the creation of the Institute of Criminal Studies, promoted by Professor En rique De Benito, was one of those experiences. With a short history, the Institute, with a multidisciplinary staff of teachers and with a program that covered the basic knowledge of Criminology, was the antecedent of the current Institute of Criminology of Valencia.